Temperature Effects on the Compressive Behaviors of Closed-Cell Copper Foams Prepared by Powder Metallurgy - Bin Han (MDPI AG, 2021)
A fabrication technology of closed-cell copper foams (CCCFs) based on powder metallurgy is proposed, by using the expanded polystyrene foams (EPS) spheres with the prescribed diameter as the space holder before sintering. The material characterization and the quasi-static compressive behaviors of both uniform and graded CCCFs at different temperatures were experimentally studied. A high temperature weakens the initial compressive modulus, plateau stress, and effective energy absorption for both uniform and graded CCCFs; meanwhile, the onset strain of densification and the maximum energy absorption efficiency are less sensitive to temperature, especially for the graded CCCFs. Compared with the uniform CCCF, the graded CCCF with even a small relative density exhibits superiority in terms of the effective energy absorption and the maximum energy absorption efficiency, attributed to the much larger onset strain of densification for the gradient pore arrangement. Finite element simulations based on the ideal sphere foam model can basically mimic the compressive performance of the CCCF samples. It is also found that both the decrease of pore diameter and the increase of cell wall thickness could improve the compressive performance of the CCCFs.